PENYUSUNAN MATERI PRESENTASI BERBASIS VIDEO - Harmastuti -; Dwi Setyowati (DHARMA BAKTI, 2018)
In introducing an institution both in the fields of education, business, business, computer information technology is very helpful both in the form of the internet and in the form of videos. Video is a very appropriate tool to promote or convey information of an institution in the form of audio visual both online and offline. This paper is an output of the implementation of community service with the theme of Preparing Video-Based Presentation Materials for student participants from the Macedonia Student Center's Child Development Center. The training discusses the steps in preparing the video, how to make or design the material to be loaded, prepare images, audio, the narrative then arranges (integrates) and selects the file format that will be used in several video software, so participants can choose video software which is considered easy. The results of community service activities, trainees understand and can practice in preparing video-based presentation material.